2012
DOI: 10.5191/jiaee.2012.19304
|View full text |Cite
|
Sign up to set email alerts
|

Information-Seeking Behavior and Utilization among Snail Farmers in Oyo State, Nigeria: Implications for Sustainable Animal Production

Abstract: The authors of this study examined the information-seeking behavior and utilization among snail farmers in Oyo State with the view of improving animal production to achieve food and nutritional security.Simple random sampling was used to select one hundred and twenty respondents out of three hundred and sixty-five registered members in Oyo state. Interview schedule was administered to elicit information relating to socio-economic characteristics, informationseeking behaviour and utilization among snail farmers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…However, there was a positive relationship between the sources of information including neighbouring farmers, other farmers and TV programmes, with the informationseeking behaviour of the farmers towards sustainable agriculture. Similarly, Owolade and Kayode (2012) concluded that there was a significant relationship between the sources of information and information-seeking behaviour of snail farmers in Oyo State, Nigeria, as well as the utilization of such information. A significant relationship also existed between constraints faced by the farmers and information-seeking behaviour, as well as utilization by these farmers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there was a positive relationship between the sources of information including neighbouring farmers, other farmers and TV programmes, with the informationseeking behaviour of the farmers towards sustainable agriculture. Similarly, Owolade and Kayode (2012) concluded that there was a significant relationship between the sources of information and information-seeking behaviour of snail farmers in Oyo State, Nigeria, as well as the utilization of such information. A significant relationship also existed between constraints faced by the farmers and information-seeking behaviour, as well as utilization by these farmers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to increase trust and open access to information, it would be important to encourage the participation of other members in communities through opinion leaders. In a study by Owolade and Kayode (2012), interpersonal means of communication were found effective for sharing information with farmers. These interpersonal relationships will help develop trust.…”
Section: Conclusion Implications Andmentioning
confidence: 99%
“…Another study in Tanzania by Benard, Dulle and Ngalapa (2014) indicated that rice farmers need information related to marketing, weather conditions, agricultural credit/loan, new seeds, storage methods, planting methods, diseases, and pest control. Owolade and Kayode's (2012) study on snail farmers in Oyo State, Nigeria, reveals that radio, television, farmers associations, newspapers and extension agents were the primary information sources to satisfy their various information needs. Another study in Nigeria by Saleh and Lasisi (2011) report agriculture, education, economy, health, and politics are some of the major information needs of rural women.…”
Section: Information Practices Of Rural Dwellers Except Fishermenmentioning
confidence: 99%
“…Several studies, such as Momodu (2002), Kalusopa (2005), Mtega (2012), Benard , Dulle and Ngalapa (2014), Owolade and Kayode's (2012), report the information practices of various rural populations including farmers, snail farmers, rural women, and cottage industry professionals. This section briefly illustrates the core findings of some of the studies conducted on rural dwellers in various countries.…”
Section: Information Practices Of Rural Dwellers Except Fishermenmentioning
confidence: 99%